Information Asymmetry and Digital Consumer Protection : A Contemporary Fiqh Muamalah Approach to Contract Legitimacy - Dwi Satri; Azis, Fakih Abdul; Nyimas Anggun Lestari; Raol, Syahria; Suriani (Fakultas Syariah IAIN Kendari, 2026)
The study aims to formulate a normative-operational analytical model concerning the obligation to provide information in digital transactions by employing contemporary fiqh muamalah principles as a benchmark for the validity of contracts (akad). The study responds to the increasing prevalence of inaccurate, incomplete, or misleading information practices in e-commerce, marketplaces, and algorithm-based services, which widen the gap between legal norms and digital market practices. It adopts a normative-qualitative approach based on library research, utilizing documentation techniques and content analysis of classical and contemporary fiqh literature, statutory regulations, fatwas, and scholarly works related to transparency, fairness, and digital consent. The data were analyzed descriptively and argumentatively to identify the relationship between muamalah principles and modern transactional practices. The findings indicate that consumer protection in digital transactions requires the integration of three core principles: transparency, fairness, and free consent. Transparency functions to reduce information asymmetry and prevent gharar (uncertainty) and ghisy (fraud) through the provision of clear, objective, and verifiable information. Fairness demands a balance of rights and obligations and the limitation of exploitation and algorithm-based price discrimination. Free consent emphasizes the necessity of voluntary agreement free from manipulative interface design or concealed pressure. These principles directly affect the validity of contracts in digital transactions. This study is limited to literature-based analysis and does not empirically examine specific platforms or conduct cross-jurisdictional comparisons. Its primary contribution lies in the systematic integration of digital consumer protection theory and the contractual validity principles of fiqh muamalah as a substantive evaluative framework for modern digital transaction legitimacy. Keywords: Fairness; Free Consent; Gharar; Muamalah; Transparency.